Research on the Online Spread of Rumors about the Quality and Safety of Agricultural Products in the New Media Era Using an Improved SEIRS Model - Qunxiang Zhang; Huilan Fang; Peng Yao; Haibin Zhang (Discrete Dynamics in Nature and Society)
The rapid development and dissemination of new media have increased online rumor transmission. Fermentation of some rumors regarding quality and safety of agricultural products has created serious problems that have negatively impacted agriculture in China and the consumption of goods such as poultry. Thus, it is imperative to explore the network dissemination mechanisms regarding how rumors about agricultural product quality and safety spread in the new media era. This study used “fast-growing chicken hormone-boosting” as the base rumor, and it developed an improved SEIRS model to identify the spread of rumors regarding agricultural product quality and safety. This study innovatively introduced a conversion rate and analyzed its impact on the secondary transmission of rumors. Using MATLAB software simulation, the research produced the following findings: an increase in netizens does not affect the threshold of rumor outbreaks; improving the immunity rate of contact netizens and the cure rate of spread netizens is the key to both controlling Internet ru`mors and reducing the contact rate of ordinary netizens. At the same time, an increase in the conversion rate could lead to a secondary outbreak of rumors.